Implementing the Quantum Learning Model to Enhance Students' Physics Learning Outcomes - Azmi, Irham; Prayogi, Saiful; Asy'ari, Muhammad (Lensa: Jurnal Kependidikan Fisika, 2023)
The students' mastery of the subject matter has been identified to not reach the attainment indicator. The low learning outcomes of the students are suspected to be a result of the predominantly lecture-based teaching method, leading to passive engagement in the learning process. This research aims to describe the improvement in students' physics learning outcomes on the topic of quantities and units using the quantum learning model. The study employed a classroom action research conducted in two cycles, including planning, implementation, observation, evaluation, and reflection stages. Twenty-seven students were involved as subjects in this research. The data on students' learning outcomes were collected using a 20-item multiple-choice test, and the evaluation of the learning process was conducted by two observers using observation sheets. The research results indicate that the students' classical mastery in the first cycle was 63.16% and increased to 85% in the second cycle. This study concludes that the implementation of the quantum learning model can enhance the physics learning outcomes of the students at MTs Nahdlatul Mujahidin NW Jempong on the topic of quantities and units.